The impact of collection and dissemination of information towards public complaint on municipal services - Zakaria, Zaherawati (2016)
The Ministry of Housing and Local Government (MHLG) has introduced the Key Performance Indicators (KPIs) to as enhance the delivery of public services to customers due to 50 per cent of complaints received were on the failure or delays in attending or responding to the needs of customers.By using quantitative method, this study attempts to examine the extent of collection and dissemination of information towards public complaints on municipal services.The finding shows the strong association between customer satisfaction and social characteristics of feedback towards complaint and information channel in Majlis Perbandaran Sungai Petani, Kedah (MPSPK).Based on the findings, in order to make customer satisfaction increase on municipal services, future strategies need to be done by focussing on the way of collection and dissemination of information among households.